SDRFHBLoc- A Secure Framework for Localization in Wireless Sensor Networks - Prashar, Deepak; Jyoti, Kiran; Kumar, Dilip (Recent Advances in Computer Science and Communications, 2020)
Background: Deployment of nodes and their security always remain the main point of concern in Wireless Sensor Networks (WSNs). Applications that are position-centric, location estimation is the major requirement and this leads to the emergence of various localization techniques. There are broadly two types of localization methods: range-based and free- range. Along with the position estimation, security of the position computation process is the prime concern as the wrong position estimation through the presence of adversaries in the environment may compromise the whole process. There are some localization systems that are estimating the position coordinate values of the nodes, but none of them has addressed the issues to overcome the inclusion of the adversaries effect on the localization process. Methods: Here, we develop and analyze a new framework SDRFHBLoc (Secure Distributed Range Free Hop Based Localization) that provides the functionality for the deployment of nodes based on different aspects like the node amount, malicious node amount, range and deployment area. Security features are also integrated in the system based on authentication of the nodes who are participating in the localization process using the signature generation and verification. Results: The proposed security framework removes the faulty nodes from the network before they participate in the localization process through the improved DV-Hop approach which is implemented in the system. Also, the optimization of the entire process provides the best and precise position estimation using the Particle Swarm Optimization (PSO) module. Conclusion: The proposed framework is quite efficient to mitigate the risk of any kind of attack possible on localization process and also customize as per the requirement of the algorithms.
Keywords: GUI